The role of soft colloidal templates in the shape evolution of flower-like MgAl-LDH hierarchical microstructures1. Issue 38 (30th April 2015) - Zhang, Jie; Xie, Xiangli; Li, Cunjun; Wang, Hai; Wang, Linjiang
<x xml:space="preserve">Abstract</x> Flower-like MgAl-SDS-LDH microstructures with a hierarchical porous structure with both large and small mesopores on their surface were synthesized by a self-assembly route, employing the anionic surfactant sodium dodecyl sulfate (SDS) as a soft template.